Efektivitas Penurunan Stres Hospitalisasi Anak dengan Terapi Bermain dan Terapi Musik - Yuni Sufyanti Arief; I Ketut Sudiana; Kristiawati Kristiawati; Dewi Indah (Jurnal Ners, 2007)
Introduction: Hospitalization in pediatric patients may caused an anxiety and stress in all age levels. Several techniques can be applied to reduced hospitalization stress in children, such as playing therapy and music therapy. The objective of this study was to analyze the difference of effectiveness between both therapies in reducing the hospitalization stress in 4-6 years old children. Method: A quasy-experimental pre-posttest design was used in this study. There were 18 respondents, divided into three groups, i.e. group one receiving playing therapy, group two receiving music therapy and the last group as control group. Data were collected by using observation sheet before and after intervention to recognize the hospitalization stress. Data were analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level of α<0.05. Result: Result showed that playing therapy and music therapy had significant effect to reduce the hospitalization stress with p=0.027 for play therapy, p=0.024 for musical therapy, and p=0.068 for control. Mann Whitney U Test revealed that there were no difference in the effectiveness of play therapy and musical therapy in reducing the hospitalization stress with p=0.009 for play therapy and control group, p=0.012 for music therapy and control group, and p=0.684 for playing therapy and musical therapy. Discussion: It can be concluded that play therapy and musical therapy are equally effective to reduce the hospitalization stress in children. It’s recommended for nurses in pediatric ward to do  playg therapy and musical therapy periodically.